A spider toxin, ω-agatoxin IV A, binds to fixed as well as living tissues: cytochemical visualization of P/Q-type calcium channels. (1st September 2016) - Nakanishi, Setsuko
Abstract : ω-Agatoxin IV A, a peptidyl toxin from Agelenopsis aperta venom, selectively binds to voltage-gated P/Q-type calcium channels. ω-Agatoxin IV A has been used as a selective tool in pharmacological and electrophysiological studies. Visualization of P/Q-type calcium channels has previously been accomplished using biotin-conjugated ω-Agatoxin IV A in freshly prepared mouse cerebellar and hippocampal slices (Nakanishi et al ., J. Neurosci. Res., 41, 532, 1995). Here biotinylated ω-agatoxin IV A was applied to transcardially fixed brain slices prepared with various fixatives. ω-Agatoxin IV A did not bind to fixed tissues from P/Q-type calcium channel knockout mice, confirming that binding to normal, fixed tissues was not an artifact. Using transmission electron microscopy, locations of biotinylated ω-agatoxin IV A binding sites visualized with gold-conjugated streptavidin showed a similar pattern to those visualized with antibody. The ability of biotinylated ω-agatoxin IV A to bind to fixed tissue provides a new cytochemical technique to study molecular architecture of synapses.